«Жіночий текст» українського модернізму в рецепції Василя Сімовича - Шелюх, Ольга; Shelіukh, Olha (Східноєвропейський національний університет імені Лесі Українки, 2016)
Коло літературних зацікавлень Василя Сімовича дуже розмаїте, й актуальні для його часу проблеми, над якими він замислювався, не втратили своєї ваги донині. Вивчаючи модерну українську літературу кінця ХІХ – початку ХХ ст., В. Сімович окремо висловив свої міркування про особливу природу «жіночого тексту» українського модернізму (насамперед творчості Лесі Українки та Ольги Кобилянської) та його рецепцію. The range of literary interests Vasyl Simovych very diverse, and issues on which he thought were relevant for both his time and not lose weight today. At the turn of XIX−XX centuries in Ukrainian literature with the emergence of women writers, born “female literary tradition”, which is the subject of many studies in literature, which was interested in the problem of female nature of the text, women reading text, reception of female creativity. So studying modern Ukrainian literature late XIX − early XX century. V. Simovich attention is paid not only to artists such words as M. Kotsіubуnskyі, O. Makovei, V. Stefanyk, Marko Cheremshyna and B. Lepkyi. Another important issue is the scientific reasoning of the special nature of their own “feminine text” Ukrainian modernism (first Lesia Ukrainka and Olha Kobylianska) and its reception. Based on the principles of receptive aesthetics of literary criticism, Vasyl Simovych his literary and critical practice proved that the works of Lesia Ukrainka, Olha Kobylianska in 20−30 years XX century. Despite the fact that were written before were frozen structure which is always perceived by all equally.
“Women Text” Ukrainian Modernism in the Reception Vasyl Simovych
Keywords: «жіночий текст»; рецепція творчості; реципієнт; естетика; мемуари; філологічний метод; “women text”; perception of the creative work; recipient; aesthetics; memoirs; philological method